Modern Age Environmental Problems and their Remediation (Springer International Publishing, 2018)
This book presents a novel picture in current advances in research of theoretical and practical frameworks of environmental problems and solutions taken from the latest empirical research findings. The book deals with basic concepts and principles of process, modern biochemical and molecular approaches, genomics and metagenomics, proteomics, remediation strategies of various hazardous pollutants, microbial carbon sequestration and remediation, phytoremediation, bioleaching, biosorption, upscaling of systems, and considers the merit and demerits based on the current literature related to environmental problems and solutions. The book is aimed at professionals, researchers, academicians, and students who would like to improve their understanding of the strategic role of environment protection and advanced applied technologies at different levels. It will be useful for the experienced engineer or scientist working in the field.